The effect of ownership structure on leverage with credit rating as a moderating variable - Harjum Muharam; Galuh Kusuma Putri (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2020)
This paper aims to examine the effect of ownership structure on leverage with credit rating as a moderating variable. The ownership structure used in this study is government ownership and managerial ownership. Leverage is measured using a debt to assets ratio (DAR). Credit rating uses ratings issued by PEFINDO.The sample used in this study was companies rated by PEFINDO and listed on the Indonesia Stock Exchange in 2015-2017. The number of samples used were 53 companies determined using a purposive sampling method. The analysis using Ordinary Least Square (OLS) regression analysis indicated that government ownership does not affect leverage, and the credit rating does not moderate the relationship between government ownership and leverage. Managerial ownership has a negative effect on leverage, and the credit rating moderates the relationship between managerial ownership and leverage